Realistic Mathematical Approach to Improve Elementary Students' Understanding of Fraction Concepts, Mathematical Thinking, and Collaboration: Systematic Literature Review - Muhadi, Andi; Wahyudin, Wahyudin; Arisetyawan, Andika (Papanda Publisher, 2025)
Fractions represent a persistent challenge in elementary mathematics education due to their abstract nature and limitations of conventional instructional approaches. Realistic Mathematics Education (RME), locally known as Pendekatan Matematika Realistik (PMR), offers a promising alternative through authentic contextualization and collaborative learning. However, no comprehensive review has examined PMR's simultaneous effects on fraction understanding, mathematical thinking, and collaboration skills. A systematic literature review following PRISMA 2020 guidelines was conducted across Scopus, ERIC, Google Scholar, and DOAJ databases for peer-reviewed studies published 2013-2023. Search strategies employed controlled keywords in English and Indonesian. Studies were included if they were empirical research focusing on PMR implementation for elementary fraction learning and measured conceptual understanding, mathematical thinking, or collaborative skills. From 935 initial records, 50 high-quality studies met inclusion criteria and underwent thematic synthesis. PMR consistently produced significant improvements across all three domains. Effect sizes for fraction understanding ranged from 0.45-0.92, with substantial gains in conceptual comprehension and real-world application abilities. Mathematical thinking development showed enhanced reasoning, problem-solving, and critical thinking skills across different ability levels. Collaborative learning outcomes demonstrated increased student engagement, motivation, and positive attitudes toward mathematics. Technology integration and teacher TPACK preparation emerged as critical amplifying factors. The findings align with Piaget's cognitive theory and Vygotsky's social constructivism, demonstrating PMR's triadic synergy of contextualization, collaboration, and cognition. This systematic review provides the first integrated evidence base showing PMR's multidimensional effectiveness in elementary fraction education, extending beyond single-domain studies to demonstrate interconnected mathematical competence development. The evidence strongly supports PMR adoption for transforming elementary mathematics instruction.